RESEARCH OF STRUCTURAL AND MECHANICAL PROPERTIES OF MEAT AS AN OBJECT OF PROCESSING IN MEAT COMMINUTOR - SYNKO, Anna (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Today, there is a rapid development of the field of information technologies, which consists of the production of information technologies and related information, which must be written in the form of documentation. Formation of documentation that will contain not only the opinion of the manufacturer, but also the consumer becomes an important task. Because in the first of all, the software is primarily user-oriented. Developers usually provide a description of the software on official sites or in data repositories. While consumers post information in virtual communities, which are rapidly gaining popularity among the population. As a result, the author developed the system architecture for the formation of software documentation based on user experience, the source of which will be virtual communities. The architecture is presented in the form of a multi-agent system, which consists of the set of interacting agents. Agents are autonomous and interactive software systems that solve certain separate tasks, activate themselves and can interact with other agents and the environment in which they function at different points in time. After studying the methods of data integration from virtual communities, the method of data consolidation was chosen. For the correct interaction of agents, each other, a consolidated data repository is used, which receives data from various virtual communities and transfers it to documentation. The system architecture includes the following agents: data collection (from various virtual communities and their transfer to the consolidated data repository); verification of information content of posts (which were obtained as a result of the work of the previous agent) for reliability and adequacy, presence of unwanted content, elimination of duplication of data; structuring community posts according to existing documentation parts; assessment of the quality of the generated documentation according to the characteristics of the ISO/IEC 25010 standard.